RAPID SLIP ALONG THE CENTRAL ALTYN TAGH FAULT: MORPHOCHRONOLOGIC EVIDENCE FROM CHERCHEN HE AND SULAMU TAGH - Mériaux A.-S.; Tapponnier P.; Ryerson F.J.; Van der Woerd J.; Finkel R.C.; Caffee M.W.; Xu X.; Xu Z. (My University, 2004)
To better constrain the ongoing rates of deformation in northern Tibet, the ages of fluvial and glacial geomorphic markers left-laterally displaced by the Altyn Tagh Fault have been determined by radiocarbon and 10Be-26Al cosmic ray exposure dating. Two sites were investigated: Cherchen He and Sulamu Tagh, both near Tura (∼37.6°N, 86.6°E). The sites are geomorphologically distinct with Cherchen He dominated by fluvial processes and the Sulamu Tagh by glacial action. Nine offsets ranging from 166 to 3660 m with ages between 6 and 113 ka yield an average slip rate of 26.9 ± 6.9 mm/yr. Landscape evolution appears to have been modulated by climate change and is temporally consistent with the δ18O record from the Guliya ice cap in the West Kunlun; the features of interest were all formed by glacial and fluvial processes subsequent to marine isotope stage 5e, with the youngest features having formed during the early Holocene Optimum. This “near-field,” morphochronological slip rate is averaged over many earthquake cycles and is hence little affected by interseismic strain. It is kinematically consistent with other, somewhat lower, geomorphic slip rate measurements to the east. The average rate, and lower bounds obtained from alternate interpretational models, 18.4 mm/yr, cannot be reconciled with the most rece geodetic measurements (∼7 mm/yr), suggesting that interseismic strain and interactions with adjacent faults may lead to disparate geologic and geodetic rate estimates. This late Pleistocene-Holocene, morphochronologic rate would imply that, at this longitude, the Altyn Tagh Fault, on the north edge of Tibet, might absorb almost as much of India's convergence relative to Siberia as the Himalayan Main Frontal Thrust does on the southern edge of the plateau.
Keywords: slip rates; cosmogenic dating; Indo-Asian collision